MUSIK MOZART MEMILIKI JUMLAH SEL GLIA TERBANYAK PADA CEREBRUM DAN CEREBELLUM RATTUS NORVEGICUS BARU LAHIR DIBANDINGKAN DENGAN GAMELAN JAWA, SUNDA DAN BALI SELAMA KEHAMILAN - Khasanah, Rima Nur; Joewono, Hermanto Tri; Widjiati, Widjiati (Universitas Tribhuwana Tunggadewi, 2021)
Intelligence is one of the basic capital in advancing a country. Efforts that can be done during pregnancy is to provide adequate nutrition and stimulation, stimulation that is easily accepted by the fetus is sound and music is the most harmonious combination of sounds. Analyzing the differences in the number of glia cerebrum cells and the newly born Rattus norvegicus cerebellum from mothers exposed to Mozart music, traditional Javanese gamelan music, Sundanese gamelan, Balinese gamelan and those who were not exposed to music during pregnancy. Experimental research with randomized post-test only control group design. Used by experimental animals Rattus norvegicus as a model of music stimulation. Cutting was done with 10 IU PMSG injection, 10 IU HCG and monomating. randomized into 5 groups. The treatment was given from 10-19 days of pregnancy, for 1 hour in the soundproof room, intensity of 65 Db. Children of Rattus norvegicus were decapitated and dissected by the brain then counted the number of glia cells using Hematoksilin - Eosin and analyzed by statistics. There were significant differences in the number of newly born Rattus norvegicus glia cerebrum cells between groups. Mozart group (25.16 ± 1.72; Astrocytes), (26.16 ± 1.50; Oligodendrocytes) and (21.40 ± 4.27; Microglia) were the highest compared to the control group, Javanese gamelan music, Sundanese, and Bali. Average Number of newborn Rattus norvegicus glia cerebellum cells in the Mozart music group (24.48 ± 3.66; Astrocytes), (19.92 ± 3.77; Oligodendrocytes) and (19.92 ± 3.86; Microglia) the highest compared to control groups, Javanese gamelan music, Sundanese gamelan, and Balinese gamelan. The Mozart exposure group had more glia cerebrum and cerebellum cells than those exposed to Javanese, Sundanese, Balinese gamelan and those who were not exposed to music.